Endogenous Symbiotic Li3N/Cellulose Skin to Extend the Cycle Life of Lithium Anode. (16th April 2021) - Luo, Yang; Li, Tianyu; Zhang, Hongzhang; Liu, Wei; Zhang, Xiaoben; Yan, Jingwang; Zhang, Huamin; Li, Xianfeng
Abstract: Nitrocellulose (NC) is proposed to stabilize the electrolytes for Li metal batteries. The nitro group of NC preferentially reacts with Li metal, and along with the cellulose skeleton is tightly wrapped on the surface, so that the polymer–inorganic double layer is formed on the Li surface. XPS profile analysis and corroborative cryo‐environmental TEM reveal that the flexible outer layer of the bilayer is a C‐O organic layer, while the dense inner layer is mainly composed of crystalline lithium oxide, lithium oxynitride, and lithium nitride. The Li deposition process was observed via in situ optical microscopy, which indicated that the NC‐derived bilayer facilitates the uniform deposition of Li ions and inhibits the growth of dendrites. After the introduction of NC into the electrolyte, the cycle life of the Li battery is twice than that of the Li battery without NC at 1.0 and 3.0 mA cm −2 . Abstract : An effective electrolyte was designed via adding nitrocellulose (NC) in ether electrolyte to form an endogenous symbiotic Li3 N/cellulose double solid electrolyte interphase (ES‐DSEI) on Li surface. An ES‐DSEI with a uniform dual‐layer provides excellent chemical and physical stability and high ionic conductivity.